Development of primary health care in Algeria - - Sidi Mohamed El-Habib Chikhi; D I Kicha; A V Tadjieva (RUDN Journal of Medicine, 2016)
The human right to health means that health services should be available to everyone. According to the literature data, the availability of medical services is associated with the level and quality of primary health care. As it was announced in 1978 at WHO conference - organization of primary health care is a key aspect of the health system. For the assessment of the health situation in Algeria, we analyzed data from the literature, the WHO data, and the results of studies in different institutions. Based on the WHO guidelines, Algeria had gradually and constantly developed primary health care facilities and trained medical staff. The assessment of progress is made on the health criteria of the population and the health development in Algeria: the crude death rate and infant mortality rate, population per medical institution and per doctor Health facilities at the primary health care system are represented by the polyclinics and the care units. The number of primary health facilities had grown rapidly during the last forty years, from 1402 to 5484 care units and from 106 to 1627 polyclinics; the number of available hospital’s beds has evolved from 43404 to 63212 beds, while the population increased from 16,370,000 to 39,500,000 inhabitants. During the same period, the number of inhabitants per clinic increased from 140,000 to 20,000 people. One care unit serves about 7,000 people, the number of inhabitants per doctor decreased from 6000 to 600 inhabitants. Population health criteria shows the decline in infant mortality from 80 per 1,000 in 1984 to 46.8 per 1,000 in 1990 due to special programs for maternal and child health care and the expanded vaccination. The average life expectancy of the inhabitants of Algeria in 2014 reached the level of 77.2 years.